Exploration of ureolytic airborne bacteria for biocementation applications from different climate zones in Japan - Meiqi Chen; Chikara Takano; Kazunori Nakashima; Sivakumar Gowthaman; Satoru Kawasaki (Scientific Reports)
Abstract The present study investigated the ureolytic airborne bacteria for microbial induced carbonate precipitation (MICP) applications, seeking resilient strains in order to address the problems of bacterial survivability and adaptability in biocementation treatment and to contribute a robust approach that can effectively stabilize diverse soils. Since the airborne bacteria tend to survive in dynamic environments, they are believed to possess remarkable adaptability in harsh conditions, thus holding great potential for engineering applications. Samplings across diverse climatic zones revealed that approximately 10–20% of the isolates were ureolytic bacteria in each sampling site. A series of characterization tests were conducted on selected strains to study the temperature dependency of urease activity. The results revealed that many of these isolates are unique in many aspects. For instance, some trains of Glutamicibacter sp. were found to precipitate extra-large calcium carbonate crystals that could be beneficial in the cementation of coarse soils. This study stands out from previous research on standard ureolytic bacteria by focusing on the exploration of airborne bacteria. The findings demonstrate that a significant number of ureolytic airborne bacteria have great potential, suggesting that the air can serve as a bacterial isolation source for MICP applications.